Advances in the Elimination of Viral Hepatitis in Mexico: A Local Perspective on the Global Initiative - Gerardo Santos-López; Arturo Panduro; Francisca Sosa-Jurado; Nora A. Fierro; Rosalía Lira; Luis Márquez-Domínguez; Marco Cerbón; Nahum Méndez-Sánchez; Sonia Roman (Pathogens, 2024)
Viral hepatitis (A–E) presents a major global health challenge. In 2015, the World Health Organization (WHO) launched an initiative to eliminate viral hepatitis, with the aim of reducing new infections by 90% and deaths by 65% by 2030. Mexico is one of 38 focus countries identified by the WHO, collectively accounting for 80% of global infections and deaths. While hepatitis B and C are commonly diagnosed in Mexico, routine diagnosis for hepatitis D and E is lacking, with no specific epidemiological data available. In 2020, Mexico implemented the National Hepatitis C Elimination Program, focusing on preventing new infections, reducing complications like cirrhosis and hepatocellular carcinoma, ensuring access to treatment, and improving patient care. However, this program has not been extended to hepatitis B and E. Addressing the challenges of viral hepatitis control in Mexico requires increased resource allocation, expanded diagnosis, vaccination for hepatitis A and B, and treatment coverage for hepatitis B and C, along with multisectoral engagement. This work provides an overview of Mexico’s response to the global initiative, highlighting its progress, challenges, and areas of opportunity.